Decomposition and release of nutrients in biomass generated by cocoa (Theobroma cacao L.) pruning in Rionegro, Santander, Colombia - Rojas-Molina, Jairo; Ortiz-Cabralez, Leidy; Escobar-Pachajoa, Laura Dayana; Rojas-Buitrago, Mervin; Jaimes-Suarez, Yeirme Yaneth (Agronomía Mesoamericana, 2021)
Introduction. Nutrient cycling plays a very important role in the sustainability of production systems. In the cocoa (Theobroma cacao L.) cultivation, the biomass decomposition generated by pruning is a fundamental basis in the dynamics of nutrients within the system. Objective. To quantify the rate of decomposition and nutrient release of different types of plant waste generated by pruning of cocoa trees. Materials and methods. The study was conducted in a cocoa farm located in Rionegro, Santander, Colombia, between June and December 2012. The rate of decomposition and nutrient release (N, P, K, Ca, Mg) was estimated in the treatments T1: leaves and twigs, T2: secondary branches and T3: primary branches, during five periods (8, 15, 23, 84 and 113 days); through decomposition bag technique. Results. The rate of decomposition and nutrient release in leaves and twigs was significantly higher at 8 days (0.1 k day-1) compared to the secondary branches (0.06 k day-1) and primary branches (0.05 k day-1). The decomposition of the secondary branches showed a tendency to be constant through time, but it was the material with the highest percentage of nutrient release at the end of the evaluation (91.4 % N; 83.67 % P; 87.40 K; 82.17 % Ca and 77.29 % Mg). Conclusion. At the beginning of the decomposition and nutrient release, the contribution of these to the system was given by the biomass obtained from leaves and twigs; however, as time progressed, the contribution was given by the biomass of secondary and primary branches with a slower nutrient release.